Aspek Sosial Dalam Drama Amangkurat-Amangkurat Karya Goenawan Mohamad - Syahrul Roziyansa (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
This research aims to determine the structure and social aspects contained in drama. There are two theories used in this research, namely structural theory and literary sociology theory. The method used in this research is the library study method with advanced techniques in the form of note-taking and writing techniques. Then proceed by using informal methods and descriptive analytical methods to analyze the data. The results of the analysis are presented using the description method. Based on the analysis carried out on the drama Amangkurat-Amangkurat, the results were found to be: First, in structural analysis which includes the characters, premise and plot depicted in the drama. Second, sociological aspects which include social, cultural, political, family and religious aspects in the drama Amangkurat-Amangkurat